Biopsy of an intracardiac paraganglioma in a dog using a fluoroscopically guided endovascular technique - Joseph S. Raleigh (Wiley, 2021)
Abstract A 10‐year‐old female spayed mixed breed dog was evaluated for diarrhea and vomiting. Diagnostic imaging demonstrated the presence of an intracardiac mass. A modified Seldinger technique was used to access the right jugular vein, and an endomyocardial biopsy forceps was introduced through a sheath to obtain several biopsies. Histopathology and immunohistochemistry demonstrated a paraganglioma. The dog underwent 1 fraction of radiotherapy and l‐asparaginase chemotherapy and was discharged. The dog developed a pulmonary thromboembolism 2 days after radiotherapy and chemotherapy, and the owner elected humane euthanasia. Although long‐term assessment of treatment response was unable to be performed, this novel diagnostic option could be considered for similar cases due to success in obtaining a histopathologic diagnosis, which is essential in developing a disease‐specific treatment plan. This report also describes the use of radiotherapy for primary treatment of an intracardiac neoplasm, which can be a consideration in the future.